Composite manganate oxygen electrode enhanced with iron oxide nanocatalyst for high temperature steam electrolysis in a proton-conducting solid oxide electrolyzer. (6th July 2015) - Li, Huaxin; Chen, Xiaoli; Chen, Shigang; Wu, Yucheng; Xie, Kui
Abstract: Composite electrode based on La0.8 Sr0.2 MnO3-δ (LSM) can be utilized in a proton-conducting solid oxide electrolyzer for steam electrolysis; however, the insufficient electro-catalytic activity of LSM still restricts the electrode performance and Faraday current efficiency. In this work, catalytic-active iron oxide nanoparticles are loaded on the surface of LSM composite oxygen electrode to improve electro-catalytic performance as well as extend the three-phase boundaries. SEM and EDS results together confirm the loading of Fe2 O3 nanoparticles with the size of approximately 20–40 nm on the surface of LSM composite oxygen electrode. The effects on electrode performance due to different contents of Fe2 O3 are loaded into LSM composite electrodes are systemically studied using symmetric cells. The electrical property of LSM is investigated and correlated to the electrochemical performance of the composite oxygen electrode in electrolysis cells. The maximum Faraday current efficiency is approximately 65% with the Fe2 O3 -loaded LSM composite electrode for steam electrolysis in a proton-conducting solid oxide electrolyzer at 800 °C. Highlights: LSM electrode with Fe2 O3 nanocatalyst shows promising electrode polarization. The dependence of electrode performance on Fe2 O3 contents is investigated. The loading of nanocatalyst significantly improves Faraday efficiency. The oxygen electrode shows stable performance for direct steam electrolysis.